Tinjauan Hukum Islam terhadap Transaksi Jual Beli Pakan Hewan Babi (Studi Kasus di Desa Kendekan): Islamic Legal Review of Pig Feed Sales Transactions (Case Study in Kendekan Village) - Musriwan, Musriwan; Andi Dahmayanti; Risdayani, Risdayani; Putra Alam; Haerul, Haerul (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyse the practice of buying and selling sweet potato leaves as pig feed in Kendekan Village, East Walenrang Subdistrict, Luwu Regency, from an Islamic law perspective. This study uses field research, through observation, interviews, and documentation. The research approach uses a normative and sociological approach with descriptive-qualitative analysis. In terms of the pillars and conditions of buying and selling, the transaction fulfils the provisions of a valid contract because it is carried out on the basis of mutual consent and the object is halal, namely sweet potato leaves. However, when viewed from the aspect of its use, this transaction falls into the category of fasid (corrupt) because it contains elements of mutual assistance in prohibited acts, as the proceeds from the sale and purchase are used to feed animals whose prohibition has been confirmed in Islamic law. The conclusion of this study states that the practice of buying and selling sweet potato leaves as pig feed in Kendekan Village is valid in terms of contract, but in substance it is not permitted in Islamic law because it contradicts the principle of sadd al-żarī‘ah. This study is expected to make a substantive contribution to the development of contemporary muamalah fiqh studies, particularly in enriching theoretical and practical perspectives in the field of Islamic economics.